2017
DOI: 10.1038/nature25452
|View full text |Cite
|
Sign up to set email alerts
|

A mildly relativistic wide-angle outflow in the neutron-star merger event GW170817

Abstract: GW170817 was the first gravitational-wave detection of a binary neutron-star merger. It was accompanied by radiation across the electromagnetic spectrum and localized to the galaxy NGC 4993 at a distance of 40 megaparsecs. It has been proposed that the observed γ-ray, X-ray and radio emission is due to an ultra-relativistic jet being launched during the merger (and successfully breaking out of the surrounding material), directed away from our line of sight (off-axis). The presence of such a jet is predicted fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
412
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(452 citation statements)
references
References 36 publications
34
412
2
4
Order By: Relevance
“…However, such a simple model fails to explain the prompt emission data of GRB 170817A (e.g., Granot et al 2017;Gottlieb et al 2018;Meng et al 2018). The brightening of the late-time X-ray/optical/radio afterglow hints the existence of a significant energy injection, which was interpreted as either lateral injection from a structured jet (Kathirgamaraju et al 2018;Lazzati et al 2018;Lamb & Kobayashi 2018;Lyman et al 2018;Xie et al 2018;Ghirlanda et al 2019;Troja et al 2018;Piro et al 2019;Xiao et al 2017) or radial injection from a stratified cocoon (Kasliwal et al 2017;Mooley et al 2018b;Nakar & Piran 2017;Margutti et al 2018). The detection of "superluminal" motion in the radio afterglow (Mooley et al 2018a;Ghirlanda et al 2019) ruled out the later scenario and reinforced the structured jet picture.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a simple model fails to explain the prompt emission data of GRB 170817A (e.g., Granot et al 2017;Gottlieb et al 2018;Meng et al 2018). The brightening of the late-time X-ray/optical/radio afterglow hints the existence of a significant energy injection, which was interpreted as either lateral injection from a structured jet (Kathirgamaraju et al 2018;Lazzati et al 2018;Lamb & Kobayashi 2018;Lyman et al 2018;Xie et al 2018;Ghirlanda et al 2019;Troja et al 2018;Piro et al 2019;Xiao et al 2017) or radial injection from a stratified cocoon (Kasliwal et al 2017;Mooley et al 2018b;Nakar & Piran 2017;Margutti et al 2018). The detection of "superluminal" motion in the radio afterglow (Mooley et al 2018a;Ghirlanda et al 2019) ruled out the later scenario and reinforced the structured jet picture.…”
Section: Introductionmentioning
confidence: 99%
“…When jets plow through dense environments they deposit a fraction of their energy in a hot cocoon (Ramirez-Ruiz et al 2002;Pe'er et al 2006), which may occur in binary neutron star mergers as the ultrarelativistic jet that powers the SGRB pushes through material ejected just before merger (Lazzati et al 2017). GRB 170817A has odd behavior in both prompt and afterglow emission, the origin of which is a matter of some debate (Abbott et al 2017a;Alexander et al 2017Alexander et al , 2018Bromberg et al 2017;Haggard et al 2017;Kasliwal et al 2017;Margutti et al 2017;Mooley et al 2018aMooley et al , 2018bTroja et al 2017Troja et al , 2018aGottlieb et al 2018;Lazzati et al 2018;Lyman et al 2018;Nynka et al 2018;Ruan et al 2018;Veres et al 2018). Possible interpretations include a structured ultrarelativistic jet (e.g., Alexander et al 2018), a jet and cocoon together (e.g., Abbott et al 2017a), or a cocoon model (e.g., Kasliwal et al 2017) where the shock breakout produces the harder peak.…”
Section: The Origin Of the Soft Tailmentioning
confidence: 99%
“…Ruan et al (2018) further found that the radio emission brightened at approximately the same rate as that of the X-ray emission, which indicates that they share a common origin (see also Mooley et al 2018). Later, Lyman et al (2018) reported that the late-time optical afterglow of GRB 170817A was continuously brightening until 110days after the merger.…”
Section: Introductionmentioning
confidence: 90%
“…The fall-back accretion process was first discussed by Colgate (1971). It is originally assumed to be Kim et al (2017), Mooley et al (2018), and Margutti et al (2018). The X-ray data points are taken from Ruan et al (2018), Lazzati et al (2017c), andD'Avanzo et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation